Dengue epidemiology in Cali, 1988-1993 (Colombia Medica, 1994)
An update on dengue and dengue hemorrhagic fever has been presented for the last few years (1988-1992) in Cali, Colombia, including the tenth epidemiological period of 1993 (2 October). A significant increase in classical dengue fever number of cases is shown, as well as those of dengue hemorrhagic fever. Between 1990 and 2 October 1993, there were 6. There were 312 cases of dengue hemorrhagic fever, although only three were confirmed.